A Stable Monomeric SiO2 Complex with Donor–Acceptor Ligands. (1st March 2017) - Rodriguez, Ricardo; Gau, David; Saouli, Jérémy; Baceiredo, Antoine; Saffon‐Merceron, Nathalie; Branchadell, Vicenç; Kato, Tsuyoshi
Abstract: Isolation of a monomeric SiO2 compound3 as a stable donor–acceptor complex with two different ligands —a σ‐donating ligand (pyridine, dimethylaminopyridine, N ‐heterocyclic carbene) and a donor–acceptor ligand (iminophosphorane)—is presented. The SiO2 complex 3 is soluble in ordinary organic solvents and is stable at room temperature in solution and in the solid state. Of particular interest, 3 remains reactive and can be used as a stable and soluble unimolecular SiO2 reagent.